Impact of the GST on the Development of Hospitality and Tourism Sector in India - Abraham, Sherry; M, , Dr. Venkataramanaiah. (International Journal of Multidisciplinary: Applied Business and Education Research, 2020)
Tourism is one of the prime activities which play a vital role not only in the generation of employment and income but also in holding firm socio-political relationship with the other countries. India is one of the most fascinating destinations to the world tourists as it is known for its diversity in culture, languages, rituals, traditions, ethnicity with rich civilization. The tourism sector in India is one of the rapidly growing sectors. It contributed 9.2 percent of GDP in 2018 and is ex-pected to contribute 9.9 percent of GDP by 2028. Goods and Service Tax (GST) is said to be a non-discriminatory tax, which affects various layers of the economy. The recent rate cuts announced by the GST council are expected to yield good results in the promotion of hospi-tality and tourism business in India. Generally, rationalization of GST rates is a positive step taken by the policymakers and it augments this sector to a great extent. It is expected that the rate cuts will give a boost to the tourism which in turn brings a good number of job op-portunities in the sector. At this juncture, an earnest attempt has been made to analyze the post-effect on the hospitality and tourism sector after the implementation of GST and the consequent amendments therein.